Research on innovation in family businesses: are we building an ivory tower?. Issue 1 (10th April 2017) - Fuetsch, Elena; Suess-Reyes, Julia
Abstract : Purpose: One of the central requirements of research is that the knowledge acquired should not only be academically rigorous, but also socially useful. If an article fails to address practical relevance, the audience will question its value and respond with "so what?". Due to recent criticism regarding the practical relevance of innovation research, the purpose of this paper is to examine whether a similar "ivory divide" prevails in research on innovation in family businesses. More specifically, this paper investigates to what extent and at what depth researchers generate practical implications for innovation in family businesses. Furthermore, different strategies to bridge the "ivory divide" are discussed. Design/methodology/approach: This literature review systematically analyses the findings of 50 journal articles focusing on innovation in family businesses published between 2004 and 2015. Based on this, the articles are classified according to their degree of practical relevance. Findings: Although the findings unanimously show the relevance of innovation for strengthening business's performance, only a minority of articles offer in-depth implications for practitioners in terms of practical guidance for action and application-oriented recommendations. A number of reasons for the development of this "ivory divide" are discussed and suggestions for how the connection between research and practice could be strengthened are provided. Originality/value: This paper attempts to provide an impulse toward more practically oriented family business research in order to increase its interestingness to academics and its value to practitioners.